Feedback. (Futurist)
Readers respond to articles that appeared in previous issues. Sister Brenda Walsh responds to “Young, Single, and Spiritual,” an article by Aaron Cohen that appeared in the July-August issue. Walsh notes that during a recent visit to her homeland of Ireland, she discovered that although it is one of the most rapidly developing countries in the world, it is very poor in terms of hope and spirituality, and many young adults are committing suicide for lack of meaning. Thomas B. Albright responds to “The 21st Century Writer,” an article by Patrick Tucker that appeared in the July-August issue. Albright asserts that the major problem with words in all languages is the separation between the voice and the written word, and he suggests that a future solution to the word problem is the creation of “Sound With Letters,” a new form of rendering pronunciation marks in writing. Bob Pisani responds to “The AI Chasers,” an article by Patrick Tucker. Pisani states that the article was fair and balanced in its assessment of the state of artificial intelligence and where it may lead.